Film Attack on Titan dalam Pandangan Filsafat Eksistensialisme Jean-Paul Sartre - Haqqi, Sabilal; Abbas, Mardhiah; Faza, Abrar M. Daud (Lembaga Yasin AlSys, 2024)
Jean-Paul Sartre is a famous figure in the fields of philoshophy and literature, considered one of the parents of contemporary existentialism. Existentialism is a philosophical school which argues that all phenomena originate from existence, or the existence of something. Existentialism is a protest against the concept of “logic” and “nature” which were emphasized in the enlightenment period (Enlightenment) in the eighteenth century. Sarte’s existentialist philosophical thought is La Liberte or human freedom. Humans are free, independent. Therefore, he must be free to determine and decide, he acts alone without other people around or with him. This research analyzes Jean-Paul Sartre's views on the theory of existentialism in the film Attack on Titan. This film is related to the theory of existentialism by Jean-Paul Sartre, a philosopher who developed the current of existentialism. By using the research method